2015
DOI: 10.1159/000430215
|View full text |Cite
|
Sign up to set email alerts
|

Mipu1 Inhibits Lipid Accumulation Through Down-Regulation of CD36 in RAW264.7 Cells

Abstract: Background/Aims: Our recent data indicated that Mipu1 overexpression reduces lipid intake and CD36 expression of macrophages in the presence of oxLDL. However, the mechanism of Mipu1 inhibiting lipid accumulation in macrophages is not elucidated. Methods: Real-time quantitative polymerase chain reaction (PCR) and western blot analysis were used to detect expression of Mipu1 and CD36. The promoter activity of CD36 was studied using luciferase assays. Chromatin immunoprecipitation (ChIP) was used to show the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Interestingly, the ZNF667 expression was reduced by siRNA, subsequently influencing the P‐selectin levels in both HDMECs subjected to H/R and HPC. These results resembled those of previous studies (Jiang et al, 2014; S. Qu et al, 2010; S. L. Qu et al, 2015); thus, we hypothesized that ZNF667 may be decreasing the endothelial adhesion by modulating P‐selectin expression (Figure 5b). EMSA has shown that a robust interaction between ZNF667 and P‐selectin probe occurs and that the mutant probe (non‐5′‐CTTA‐3′core sequence) failed to bind to ZNF667.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the ZNF667 expression was reduced by siRNA, subsequently influencing the P‐selectin levels in both HDMECs subjected to H/R and HPC. These results resembled those of previous studies (Jiang et al, 2014; S. Qu et al, 2010; S. L. Qu et al, 2015); thus, we hypothesized that ZNF667 may be decreasing the endothelial adhesion by modulating P‐selectin expression (Figure 5b). EMSA has shown that a robust interaction between ZNF667 and P‐selectin probe occurs and that the mutant probe (non‐5′‐CTTA‐3′core sequence) failed to bind to ZNF667.…”
Section: Discussionsupporting
confidence: 91%
“…The ZNF667 expression in flap tissues also was much higher in the RIPC group. ZNF667 functioned as nuclear transcription repressors, negatively regulated Bax or CD36 (Jiang et al, 2014; S. Qu et al, 2010; S. L. Qu et al, 2015), but the downstream target gene is still not well documented in skin microvessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZNF667 (zinc finger protein 667, also referred to as Mipu1) participates in cell growth, apoptosis, oxidative stress, and lipid accumulation. In a study on laryngeal squamous cell carcinoma (LSCC), it was found that ZNF667 is a tumor-suppressing gene [64][65][66][67][68]. ZNF667 can regulate P-selectin expression in specific cells and leukocyte-endothelial adhesion after hypoxia [69].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF667 also mediates cytoprotection of HIF1 against hydrogen peroxide-mediated injury in H9c2 cells through transcriptional repression of BAX (25). In addition, ZNF667 can inhibit oxLdL-induced foam cell formation, cell apoptosis and lipid accumulation in macrophages by directly inhibiting the transcription of cd36 (38,39). Nonetheless, to date, no angiogenesis-related gene has been identified as the direct target gene of ZNF667.…”
Section: Discussionmentioning
confidence: 99%